Fungal strain impacts the shape, bioactivity and multifunctional properties of green synthesized zinc oxide nanoparticles. (May 2019) - Mohamed, Asem A.; Fouda, Amr; Abdel-Rahman, Mohamed Ali; Hassan, Saad El-Din; El-Gamal, Mamdouh S.; Salem, Salem S.; Shaheen, Tharwat I.
Abstract: This work aimed to investigate the influence of fungal strains onto shape, functional properties, and potential applications of biosynthesized nanoparticles (NPs). The aqueous extract of two newly isolated fungal strains, Fusarium keratoplasticum strain (A1-3) and Aspergillus niger strain (G3-1), were used for synthesis of ZnO-NPs. Nanoparticles formation was confirmed by visual observation of color change and UV–visible spectroscopy. The morphological and structural properties of NPs were analyzed by Transmission Electron Microscope (TEM), Fourier Transform Infrared Spectroscopy (FT-IR), X-Ray Diffraction (XRD), Dynamic Light Scattering (DLS) and zeta potential analyses. Different ZnO-NPs shapes were obtained; where, F. keratoplasticum strain (A1-3) synthesized hexagonal NPs and A. niger strain (G3-1) synthesized nano-rod shape NPs. The antibacterial activities against Gram-negative and Gram-positive bacteria as well as in vitro cytotoxicity against three different animal cell lines exhibited that biocidal activity of NPs is a shape-dependent. Furthermore, nanoparticle shapes greatly affected the multifunctional properties of textile fabrics coated with ZnO-NPs. Nano-rod NPs showed enhanced antibacterial properties against pathogenic bacteria and UV-protection index compared to the hexagonal ZnO-NPs. Therefore, this work provides a gateway to explore shape-dependent properties of biologically synthesized NPs and their potentiality to be utilized for specific applications. Graphical abstract: Image 1 Highlights: The The shape of the biosynthesized ZnO nanoparticles (NPs) is strain-dependent. Fusarium keratoplasticum strain (A1-3) synthesize hexagonal ZnO-NPs. Aspergillus niger strain (G3-1) synthesize nanorod ZnO-NPs. Bioactivity and multifunctional properties of green ZnO-NPs are shape-dependent. Nanorod NPs exhibited enhanced bactericidal activity and UV protection as fabrics coating materials.